Efforts to Improve Students’ Self-Confidence in Peer Social Interaction through Person-Centered Group Counseling: Upaya Meningkatkan Kepercayaan Diri Siswa dalam Bergaul dengan Teman Sebaya melalui Konseling Kelompok Person Centered - Fauzia Safitri; Azam Arifyadi; Bau Ratu; Dian Fitriani (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2025)
This guidance and counseling action research was conducted in response to seventh-grade students’ low self-confidence in peer interaction, which may hinder healthy social adjustment at school. The study aimed to examine whether person-centered group counseling could improve students’ self-confidence through two action cycles. Eight students of SMP Negeri 19 Palu (academic year 2024/2025) were purposively selected from an initial screening of all Grade VII students based on low self-confidence scores and age criteria (13–15 years). The intervention followed Kemmis and McTaggart’s cyclic model (planning, action, observation, reflection), with success indicators defined operationally as: (a) an increase in the group’s mean self-confidence score from the low category to at least the moderate category in Cycle I, and (b) at least 75% of participants reaching the high category in Cycle II. Self-confidence was measured using a peer-interaction self-confidence questionnaire consisting of [insert number of items] items across [insert dimensions] dimensions, validated by [insert method, e.g., CVI/FA] and showing reliability of α/ω = [insert value]. Descriptive statistics showed that the pre-cycle scores were entirely in the low category (M = 35.13, SD = 7.64). After Cycle I, three students moved into the moderate category while five remained low, indicating partial improvement. In Cycle II, seven students reached the high category and one remained moderate, suggesting that person-centered group counseling was effective in enhancing students’ self-confidence in interacting with peers.